2011
DOI: 10.1111/j.1365-2559.2011.03966.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and immunohistochemical analysis of spindle-cell carcinoid tumour of the lung

Abstract: SCCTs are clinically asymptomatic, peripherally located, well-demarcated tumours, and patients with SCCTs have a favourable outcome. The immunoreactivity pattern of SCCT (low reactivity of broad-spectrum CK and reactivity for vimentin in intratumoral sustentacular cells) might result in a misdiagnosis of SCCT as mesenchymal tumour; therefore, pathologists need to be familiar with this pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Neuroendocrine neoplasms may show spindle-shaped nuclei rather than their more typical epithelioid nuclei. 10,11 To further complicate matters, GISTs may potentially express a range of neuroendocrine markers, 12,13 and synovial sarcomas commonly express CD56, 14 as was indeed demonstrated by all four presented cases. However, all four cases showed morphological features more typical of synovial sarcoma than of neuroendocrine neoplasm, i.e.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Neuroendocrine neoplasms may show spindle-shaped nuclei rather than their more typical epithelioid nuclei. 10,11 To further complicate matters, GISTs may potentially express a range of neuroendocrine markers, 12,13 and synovial sarcomas commonly express CD56, 14 as was indeed demonstrated by all four presented cases. However, all four cases showed morphological features more typical of synovial sarcoma than of neuroendocrine neoplasm, i.e.…”
Section: Discussionmentioning
confidence: 52%
“…The differential diagnosis of neuroendocrine neoplasm is particularly relevant to tumours arising within the retroperitoneum and therefore, potentially, the pancreas. Neuroendocrine neoplasms may show spindle‐shaped nuclei rather than their more typical epithelioid nuclei . To further complicate matters, GISTs may potentially express a range of neuroendocrine markers, and synovial sarcomas commonly express CD56, as was indeed demonstrated by all four presented cases.…”
Section: Discussionmentioning
confidence: 59%
“…For example, a high positive rate of TTF-1 is seen in spindle cell carcinoid tumors. 18 Furthermore, the variation in the criteria for a positive stain in these studies may be another factor contributing to the great variation of results. In our current study, 33% of TCs and 50% of ACs demonstrated some degree of immunoreactivity for TTF-1, which is consistent with the previously reported study using similar scoring criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The reported rates of TTF-1 positivity in pulmonary carcinoids range from 0% to 69%, using the same monoclonal 8G7G3/1 antibody. 9,17,18 The wide range of reported TTF-1 positivity in carcinoids may be partially attributed to the case selection. For example, a high positive rate of TTF-1 is seen in spindle cell carcinoid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In Tsuta K et al. 1 , parts C and D were missing from Figure 4. Figure 4 should have appeared as follows:…”
mentioning
confidence: 99%